The Utilised Unmanned Aerial Vehicles in Forest Plantation Maintenance - Zuhdi Yahya; Dwi Ery Mujahiddin; Rendy Setiawan; Akas Pinaringan Sujalu (Jurnal Penelitian Pendidikan IPA, 2025)
The use of drones has progressed, including being used in the forestry sector, especially in Industrial Plantation Forests as an operational tool in preparation activities before planting (pre planting spraying). This research was conducted in the PT Surya Hutani Jaya Industrial Plantation Forest area, in Kutai Kartanegara Regency, using a using the purposive sampling method on work plots that have become target work locations with the aim of knowing the efficiency of labour in pre-planting spraying activities and knowing the effectiveness of spraying activities using drones. The productivity of drone spraying activities can reach 23.21 Ha / Day compared to conventional spray which only has a productivity of 0.5 Ha / Day, so that to meet the company's planting target in May 2023 covering 600 Ha requires only 1 drone spraying tool while conventional spray 48 people. This shows that the efficiency value of using spraying drone work tools has increased very rapidly reaching 4.624%. As for the spray results from observations that have been made, the target is that the weeds experience evenly distributed death so it is very good to be recommended as a supporting work tool to achieve the targets given by the company.